FEATURES OF PSYCHOLOGICAL ASSISTANCE FOR VICTIMS OF SCHOOL BULLYING (Psychology Travelogs, 2023)
The article is devoted to the actual problem of school violence in interpersonal relationships in the educational space. The article offers an overview of the manifestations of bullying in the behavior of schoolchildren, the characteristic features of school bullying and its impact on the development of a child's personality, common features of anti-bullying programs that are used in different countries of the world.Contemporary Ukrainian society recognizes the existence of the problem of child abuse and the need to take measures to improve the system of prevention, detection and overcoming of this phenomenon. Educational institutions set themselves the goal of comprehensive development of the child, creation of conditions for assimilation of effective models of behavior with peers, however, frequent phenomena of school bullying and high level of conflict among children do not allow to fully achieve the set goals. At present, taking into account external challenges, such as war, pandemic, etc., the extremely important task is to create a safe educational environment to prevent and fight against the negative consequences of the phenomenon of school violence.The work describes the algorithm of conducting a dialogue between a psychologist and a child victim of school bullying, which includes: establishing a trusting relationship between the child and the psychologist; an expression of sympathy; reducing the feeling of guilt; support and approval of the child's behavior; finding reserves of support and assistance; creating conditions for stopping violence and developing a behavior strategy; supporting the child's determination.The article reveals the stages of dialogue between a psychologist and a child victim or witness of violent acts, which included: the preliminary stage; introductory stage; stage of free narration; stage of detailed questions; the final stage.The author of the article substantiates the fact that the peculiarities of psychological assistance to victims of school bullying are the psychologist's observance of the specified communication algorithm and the stages of conversation with a child victim or witness of violent acts.
Keywords: bullying; school violence; educational space; psychological help; victim